Sanctity (wilayah) in Islamic Mysticism - Asadallah Shukriyan (حکمت اسرا, 2010)
The idea of ‘sanctity’ or ‘grace’ (walÁyah) in Islamic mysticism paints such a realistic and sacred picture of the universal order that it reveals the existence of a nexus that transcends all lower delimitations and that ties the Perfect Man to Reality as such. The article that follows goes through various religious and mystical texts so as to present a clear picture of walÁyah. It continues by investigating its various divisions and dimensions, as well as its concomitants and particularities in Islamic mysticism.